An unusual case of aortopulmonary window with crossed pulmonary arteries. Issue 2 (29th November 2021) - Verma, Mansi; Pandey, Niraj Nirmal; Kumar, Sanjeev; Ramakrishnan, Sivasubramanian
Abstract: We report a case of a 4‐year‐old boy with a distal type of aortopulmonary window with crossed arrangement of the pulmonary arteries. This case highlights the potential clinical implications of this variant pulmonary arterial anatomy in the setting of the aortopulmonary window and the role of computed tomography angiography in accurately defining vascular relationships in patients with complex congenital cardiac defects.